Exploring the use of high and low demand simulation for human performance assessment during multiorgan retrieval with the joint scrub practitioner. (21st May 2020) - Morozova, Gala; Martindale, Amanda; Richards, Hugh; Stirling, John; Currie, Ian
Abstract : Introduction: The National Organ Retrieval Service (NORS) 2015 review recommended a Joint Scrub Practitioner for abdominal and cardiac teams during combined organ retrieval. To evaluate the feasibility of this role, and to understand the functional implications, this study explores the use of simulation and provides a novel and comprehensive approach to assess individual and team performance in simulated multiorgan retrievals. Methods: Two high-fidelity simulations were conducted in an operating theatre with porcine organs, en bloc, placed in a mannequin. For donation after brainstem death (DBD) simulation, an anaesthetic machine provided simulated physiological output. Retrievals following donation after circulatory death (DCD) began with rapid arrival in theatre of the mannequin. Cardiothoracic (lead surgeon) and abdominal (lead and assistant surgeons; joint scrub practitioner, n=9) teams combined for the retrievals. Data collected before, during and after simulations used self-report and expert observers to assess: attitudinal expectations, mental readiness, mental effort, non-technical skills, teamwork, task workload and social validation perceptions. Results: Attitudinal changes regarding feasibility of a joint scrub practitioner for DBD and DCD are displayed in the main body. There were no significant differences in mental readiness prior to simulations nor in mental effort indicated afterwards; however, variance was noted between simulations for individual team members. Non-technical skills were slightly lower in DCD than in DBD. Global ratings of teamwork were significantly (p<0.05) lower in DCD than in DBD. Measures of attitude indicated less support for the proposed joint scrub practitioner role for DCD than for DBD. Discussion: The paper posits that the joint scrub practitioner role in DCD multiorgan retrieval may bring serious and unanticipated challenges. Further work to determine the feasibility of the NORS recommendation is required. Measures of team performance and individual psychological response can inform organ retrieval feasibility considerations nationally and internationally.